1970 British Cohort Study. (16th October 2014) - Brown, Matt
The 1970 British Cohort Study (BCS70) is one of Britain's world famous national longitudinal birth cohort studies, three of which are run by the Centre for Longitudinal Studies at the Institute of Education, University of London. BCS70 follows the lives of more than 17, 000 people born in England, Scotland and Wales in a single week of 1970. Over the course of cohort members lives, the BCS70 has collected information on health, physical, educational and social development, and economic circumstances among other factors. Since the birth survey in 1970, there have been nine 'sweeps' of all cohort members at ages 5, 10, 16, 26, 30, 34, 38 and most recently at 42. Data has been collected from a number of different sources (the midwife present at birth, parents of the cohort members, head and class teachers, school health service personnel and the cohort members themselves). The data has been collected in a variety of ways including via paper and electronic questionnaires, clinical records, medical examinations, physical measurements, tests of ability, educational assessments and diaries. The majority ofBCS70 survey data can be accessed by bona fide researchers through theUK Data Service at the University of Essex.